Noma management in a child with systemic lupus erythematosus - Irna Sufiawati; Asri Arum Sari; Budi Setiabudiawan; Rahmat Gunadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Noma, also known as cancrum oris, is an orofacial gangrene, which during its fulminating stage causes progressive and mutilating destruction of the infected tissues. The disease occurs mainly in children with malnutrition, poor oral hygiene and debilitating concurrent illness. Purpose: The aim of this paper was to report a unique case of noma associated with systemic lupus erythematosus in an 8-year-old boy. Case: An 8-year-old boy referred to Oral Medicine Department complaining about an ulcer at the left corner of his mouth for 1 month, painful and difficulty in opening the mouth. The patient was diagnosed systemic lupus erythematosus since 14 months before and had been given immunosuppressive therapy. The patient was also diagnosed severe malnutrition. Haematologic investigations revealed anemia. Case management: Panoramic radiography was performed to check for dental or periodontal foci of infection, but no abnormalities were present. The microbiology examination revelaed Fusobacterium necrophorum, Staphylococcus aureus, and Klabsiella. The patient has been treated with oral irrigation using hydrogen peroxide, saline and 0.2% chlorhexidine, thus helped to slough the necrotic tissue. Oral antibiotics and analgesics were prescribed. The patient was admitted to hospital under the care of a pediatrician, allergy and immunology specialist, and a nutritionist. The result of the comprehensive disease management showed that the lesion healed completely, but leaving a scar on his corner of the mouth. Its physical effects are permanent and may require reconstructive surgery to be repaired by oral surgeon. Conclusion: Noma is not a primary disease, there are various predisposing factors usually precede its occurrence. The management of noma requires a multidisciplinary approach.Latar Belakang: Noma, dikenal sebagai cancrum oris, adalah gangren pada daerah orofasial, yang menyebabkan kerusakan progresif dari jaringan yang terinfeksi. Penyakit ini terjadi terutama pada anak dengan gizi buruk, kesehatan mulut yang buruk dan penyakit yang melemahkan. Tujuan: Makalah ini bertujuan untuk melaporkan sebuah kasus noma yang unikpada seorang anak laki-laki berusia 8 tahun yang menderita lupus eritematosus sistemik. Kasus: Seorang anak laki-laki 8 tahun dirujuk ke Bagian Ilmu Penyakit Mulut, mengeluh adanya luka di sudut mulut sebelah kiri yang telah diderita selama 1 bulan, terasa sangat sakit dan sulit membuka mulut. Pasien didiagnosis lupus eritematosus sistemik sejak 14 bulan sebelumnya dan telah diberikan terapi imunosupresif. Pasien juga didiagnosis menderita malnutrisi yang berat. Pemeriksaan hematologi menunjukkan pasien menderita anemia. Tatalaksana kasus: Radiografipanoramik dilakukan untuk memeriksa fokus infeksi dental atau periodontal, tetapi tidak ditemukan adanya kelainan. Pada pemeriksaan mikrobiologi ditemukan adanya Fusobacterium necrophorum, Staphylococcus aureus, dan Klabsiella. Perawatan pada pasien meliputi irigasi pada daerah gangren dengan hidrogen peroksida, larutan salin dan klorheksidin 0,2% untuk membersihkan jaringan nekrotik. Pasien juga diberikan antibiotik dan analgesik. Pasien dirawat di rumah sakit di bawah perawatan dokter spesialis anak, dokter spesialis alergi imunologi, dan ahli gizi. Hasil penatalaksanaan penyakit secara komprehensif memperlihatkan adanya penyembuhan, tetapi meninggalkan jaringan parut pada sudut mulutnya. Kelainan fisik tersebut bersifat permanen dan memerlukan pembedahan rekonstruktifoleh dokter gigi spesialis bedah mulut. Kesimpulan: Noma bukanlah penyakit primer, terdapat berbagai faktor predisposisi yang biasanya mendahului terjadinya penyakit tersebut. Pengelolaan noma memerlukan pendekatan multidisiplin.